2013 13th International Conference on ITS Telecommunications (ITST) 2013
DOI: 10.1109/itst.2013.6685545
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a non-line-of-sight path-loss model for V2V communications at street intersections

Abstract: Abstract-In this paper a non-line-of-sight (NLOS) path-loss and fading model developed for vehicle-to-vehicle (V2V) communication at 5.9 GHz is validated with independent and realistic measurement data. The reference NLOS model is claimed to be flexible and of low complexity, and incorporates specific geometric aspects in a closed-form expression. We validated the accuracy of the model with the help of realistic channel measurements performed in selected street intersections in the city of Lund and Malmö, Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…In the model C=3.75 dB is the so-called curve shift, L S U =2.94 dB is the sub-urban loss, i s =0 is the urban loss factor, i s =1 the sub-urban loss factor, E L =2.69 is the loss exponent, E S =0.81 is the street exponent, E T =0.957 is the TX distance exponent, and finally d b =180 m is the break even distance. The model was later validated by independent measurement data by Abbas et al [40] with good agreement, but also with the suggestion to include a random offset parameter to reflect variations between different street intersections; random variations were also suggested in [41] based on the comparison of ray tracing results with the model of [42]. Delay Dispersion: As far as the delay dispersion is concerned, the rms delay spread (second central moment of the power delay profile) for V2V environments varies as a function of location, and can be modeled as a random variable (log normally distributed in most cases).…”
Section: Device-to-device Modelsmentioning
confidence: 99%
“…In the model C=3.75 dB is the so-called curve shift, L S U =2.94 dB is the sub-urban loss, i s =0 is the urban loss factor, i s =1 the sub-urban loss factor, E L =2.69 is the loss exponent, E S =0.81 is the street exponent, E T =0.957 is the TX distance exponent, and finally d b =180 m is the break even distance. The model was later validated by independent measurement data by Abbas et al [40] with good agreement, but also with the suggestion to include a random offset parameter to reflect variations between different street intersections; random variations were also suggested in [41] based on the comparison of ray tracing results with the model of [42]. Delay Dispersion: As far as the delay dispersion is concerned, the rms delay spread (second central moment of the power delay profile) for V2V environments varies as a function of location, and can be modeled as a random variable (log normally distributed in most cases).…”
Section: Device-to-device Modelsmentioning
confidence: 99%
“…Intersections are a challenging environment for V2V wireless communication, as the V2V communication links may be blocked by high-rise buildings and other obstructions. Measurements have shown that the strength of the received signal power reduces quickly with distance from the intersection [7][8][9][10][11][12][13], resulting in significant degradation of V2V transmission performance; the packet delivery ratio reduced notably at distances of 40-50 m from the intersection [10]. Moreover, the data packet collision problem tends to be more severe at intersections, as the vehicle density is usually higher at an intersection than in other places.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the transmission range of each vehicle is the same and constant, and vehicles move straightly at a constant speed in those protocols. They ignore the channel state information and the mobility model that characterizes the individual, which are important factors to calculate the link stability [3]. Therefore it increases the difficulty to apply the traditional protocols into reality.…”
Section: Introductionmentioning
confidence: 99%